Use of health services by older adults at the Regional Hermilio Valdizán Medrano Hospital - Ramos-Alania, Abner (2020)
The objective of the research was to describe the use of health services by the elderly users of the Regional Hospital Hermilio Valdizán Medrano, 2019. It was a descriptive, cross-sectional and correlational study, the probabilistic sample of which was made up of 138 mature adults. An interview guide and a record sheet on the use of health services, previously validated and made reliable, were used. Ethical considerations for research were applied. Descriptive analysis was performed and hypotheses were tested using X2 for p≤0.05. According to the results, the majority of older adults were continuators [71.7% (99)], the main reason for consultation was chronic degenerative-type disease [37.0% (17), followed by infections [28.3% (39)]. In 17.4% (24), the main cause of hospitalization in the last episode was Acute Respiratory Infection, in 15.2% (21) diabetes mellitus and cardiovascular problems. Regarding the use of health services according to sociodemographic characteristics, 26.1% (36) of male adults used them continuously, while 39.1% (54) of women were discontinuous. 19.6% (27) of those between 70-79 years of age; 37.0% (51) and 13.0% (18) of those who had no educational level and primary level respectively, 32.6% (45) whose income was between 500-799 soles and 30.4% (42) of income ≤ 499 soles, used the services continually. These correlations were significant (p ≤0.05) and it is concluded that the sociodemographic variables are related to the use of health services by older adults at the Hermilio Valdizán Medrano Regional Hospital.